The Challenges of Selective Mining within the Globe Progress Gold Mine, Reefton, South Island, New Zealand - R Cooksey (The Australasian Institute of Mining and Metallurgy, 2011)
The Globe-Progress Mine is an open pit gold mine that is part of the larger Reefton Goldfields deposit located on the West Coast of New Zealand. The regional geology comprises a series of north to south oriented fold structures that have undergone post-deformation mineralisation. The structural geology within the mine itself is more complex, with major shears hosting numerous high-grade mineralised quartz shoots and splays that have been historically mined.The selective mining of ore within the pit is challenging due to the orientations of the hanging wall and footwall areas of the main Globe shear zone, the lithologies of these areas which range from highly brecciated and sheared material to competent mineralised host rock, and in the hazards presented by the numerous old historic underground workings. The coordination of drilling, modelling and excavation of the ore requires careful planning to maximise recovery whilst operating with the pit design boundaries.Grade control packages are custom designed to reflect the orientation of the footwall and hanging wall mineralisation. The shear material in the footwall zone dips between 60° and 70° and requires angled drilling whereas the footwall mineralisation is contained in shallow dipping quartz veins sub parallel to bedding and can be vertically drilled to best intercept the mineralisation. Ore excavation is directed so that the contact between the footwall and hanging wall is mined in the correct direction so that any non-visual ore contacts can be safely mined and that the ore-waste dilution is reduced.The ongoing grade control and selective mining of the Globe Progress deposit continues to deliver high grade ore for processing by ensuring that waste and dilution of ore is reduced and that recovery is maximised.